The problem of proper use of water resources - Prof. Khamidov G; Kholmatova Sh.M,; Teacher Tadjibayeva L.А (Global Scientific Publishing, 2023)
The article deals with modern problems of water resources protection. For at least two millennia, water quality has been steadily deteriorating and reaches levels of pollution where the use of water for various purposes is severely limited or water can be harmful to humans. This deterioration is associated with socio-economic development within the river basin, but long-range atmospheric transport of pollutants has now changed this condition: even remote areas can be polluted.
Keywords: Hydrological and environmental factors; rational use of thermal and biological energy; suspended particles; wastewater